Business Model Canvas as a Strategy for the Development of BUMDES in Kuningan Regency in the Perspective of Islamic Economics - Siti Komara (Eduvest - Journal of Universal Studies, 2025)
Bumdes, if managed properly, can make a village an independent village and be able to improve community welfare. The purpose of this research is to analyze the condition of BUMDes from a business aspect using BMC and VPC, analyze the condition of BUMDes based on the perspective of Islamic economics and formulate strategies for the development of BUMDes to be more optimal so that it is able to improve people's welfare. The type of research used is qualitative with a data collection method using observation, interviews and documentation conducted on Bumdes/Village Head managers and the community. Data analysis using SWOT Analysis and data triangulation. The results of the study show that the implementation of BMC and VPC is effective in meeting local needs, empowering communities, and creating relevant value. However, challenges such as limited funding, lack of strategic partnerships, and low adoption of local products remain obstacles that need to be overcome. The implementation of BUMDes management based on Islamic economic values in the four villages shows initial success in creating positive social and economic impacts. However, great potential to improve community welfare and business sustainability can still be explored through more integrated and innovative strategies